Perlindungan Hukum Jaminan Sosial Pekerja Dengan Perjanjian Kerja Waktu Tertentu (PKWT) Di Indonesia - Cahyaalamsah, Cuncun; Sagita, Hadi; Wibowo, Goesti Dimas; Fairuzy, Fakhri Ramdhani; Kartika, Yuniar Ayu (Journal of Industrial Relations Studies, 2025)
The abstract contains the objectives, methods of analysis and conclusions. The Social security is a fundamental right of every worker, guaranteed by Indonesian legislation. Workers under Fixed-Term Employment Agreements (PKWT) are normatively entitled to the same rights as permanent workers in accessing social security programs administered by the BPJS for Employment (BPJS Ketenagakerjaan). These programs include the Old Age Security (JHT), Pension Security (JP), Work Accident Security (JKK), and Death Security (JKM). However, in practice, many PKWT workers do not receive these entitlements due to various obstacles. This research employs a normative juridical approach by reviewing legal provisions such as the 1945 Constitution, Law No. 40 of 2004, Law No. 24 of 2011, Law No. 13 of 2003, and Government Regulation No. 35 of 2021. The findings reveal that the main barriers include the low legal awareness of employers, weak labor supervision mechanisms, and limited legal literacy among workers. Therefore, it is necessary to strengthen regulations, improve legal education, and optimize the role of BPJS in reaching all workers, including those with temporary employment status, in order to realize fair and inclusive social protection